SAHARAPONICS project: Local production of food of high nutritional quality and minimal water consumption in refugee camps in arid areas - Javier Marugán; Cristina Pablos; Loïc Le Goueff; Malad Mohamed Sidi; Fatimetu Omar Mohamed (Societal Impacts)
Due to water shortages, the Sahrawi refugee communities located in Tindouf (Algeria) suffer structural nutritional deficiencies derived from their diet based mainly on carbohydrates (rice, cereals, sugar) supplied by the World Food Bank due to the logistical difficulties of transport to the Sahara Desert. The SAHARAPONICS project has made it possible to develop systems for the local production of high-quality protein foods (fish) and vegetables rich in vitamins and minerals that can reduce the incidence of anaemia in fertile women in the communities and indicators of propensity to diabetes in the general population. To this end, a low water consumption aquaponic system has been designed based on locally available materials. The project has included the development of assembly and operation documentation in the local language and the training of responsible personnel to ensure the replicability and long-term use of the systems. Although the implementation generates significant changes in the daily lives of the inhabitants, increasing their workload, the long-term benefits, in terms of food security, economic development, and empowerment, outweigh the initial challenges. Beyond the expected impact on the improved use of water, provision of food and improvement of health, the technology also generated economic opportunities for vulnerable communities in a sustainable way. The users' feedback pointed out optimistic evidence and insights into the potential long-term impacts of the technology, supporting aquaponics as a successful concept that shows the community the possibility of producing high-nutritional-value food with very low water consumption using innovative systems based on locally available materials.